LANDASAN TEORI, KERANGKA BERFIKIR, DAN PENGAJUAN HIPOTESIS DALAM PENELITIAN KUANTITATIF - Sari, Windy Dian (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2024)
This paper describes the theoretical basis, framework of thinking, and hypotheses. The writing uses a qualitative approach to literature study to describe the desired data. The results of the study indicate that a researcher or writer of scientific work needs to understand the theory used for his research. An understanding of the theory can guide researchers in preparing the next stage of problem solving. In addition to theory, researchers or scientific paper writers can develop a framework of thinking and research hypotheses. The framework of thinking helps researchers develop research steps. Meanwhile, the hypothesis helps researchers understand the framework of the expected findings